In vitro anti-cholinesterase and antioxidant activity of extracts of Moringa oleifera plants from Rivers State, Niger Delta, Nigeria - Nwidu, Lucky Legbosi; Elmorsy, Ekramy; Aprioku, Jonah; Siminialayi, Iyeopu; Carter, Wayne (MDPI, 2018)
This study evaluated Moringa oleifera extracts from two locations in Niger Delta for in vitro anti-cholinesterase and antioxidant activities. Methanolic, aqueous and ethanolic extracts of Moringa oleifera were evaluated for inhibition of acetylcholinesterase (AChE) activity, antioxidant properties, and total phenolic and flavonoid contents using standard procedures. M. oleifera extracts possessed significant and concentration dependent AChE inhibitory activity for methanolic, aqueous, and ethanolic extracts. For the most potent extracts, the percentage AChE inhibition/IC50 (µg/mL) values were Moringa oleifera root methanolic extracts (MORME): ~80%/0.00845; Moringa oleifera root ethanolic extract 1 (MOREE1): ~90%/0.0563; Moringa oleifera root ethanolic extract 2 (MOREE2): ~70%/0.00175; and Moringa oleifera bark ethanolic extract (MOBEE): ~70%/0.0173. The descending order of AChE inhibitory potency of plant parts were: root > bark > leaf > flowers > seed. All M. oleifera methanolic extracts at a concentration of 1000 µg/mL displayed significant (p < 0.05–0.001) DPPH radical scavenging activity, with values of ~20–50% of that of ascorbic acid. The total phenolic content and total flavonoid content (TPC/TFC) of MORME, Moringa Oju bark methanolic extract (MOBME), MOREE1, MOREE2 and Moringa leaf ethanolic leaf extract (MLEE) were (287/254), (212/113), (223/185), (203/343) and (201/102) mg gallic acid equivalents/g and quercetin equivalents/g, respectively. There was an inverse correlation between plant extract AChE inhibition and total phenolic (p < 0.0001) and total flavonoid contents (p < 0.0012). In summary, this study revealed 5 of 19 extracts of M. oleifera that have potent in vitro anti-cholinesterase and antioxidant activities.